2015
DOI: 10.1080/07370016.2015.1026158
|View full text |Cite
|
Sign up to set email alerts
|

Illuminance, Subjective Sleep Quality, and Psychosomatic Health in Elderly Individuals Requiring Care: A Survey of Japan’s Hokuriku Region in Winter

Abstract: We measured the illuminance exposure for 3 days in winter of a convenience sample of 44 elderly people certified as requiring support in Japan's Hokuriku region. We calculated the illuminance ratio per minute during activity and while in bed and analyzed the relationship between illuminance, subjective sleep quality, and psychosomatic health. There was a significant negative correlation between illuminance and 15-item Geriatric Depression Scale scores. Multiple regression analysis indicated that depression sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Some scholars studied the sleep quality of European older adults and reported that the prevalence of disorders of sleep ranged from 16.6% to 31.2%, and sleep quality was highly associated with mental illness [62]. A study on sleep quality and psychological factors among Japanese older people reported that the sleep quality of older adults was significantly correlated with de-pression [63]. Previous findings showed that the risk of depression in older adults is significantly higher compared with that of non-sleep disorder group.…”
Section: Perceived Social Support Rumination and Sleep Quality Are Co...mentioning
confidence: 99%
“…Some scholars studied the sleep quality of European older adults and reported that the prevalence of disorders of sleep ranged from 16.6% to 31.2%, and sleep quality was highly associated with mental illness [62]. A study on sleep quality and psychological factors among Japanese older people reported that the sleep quality of older adults was significantly correlated with de-pression [63]. Previous findings showed that the risk of depression in older adults is significantly higher compared with that of non-sleep disorder group.…”
Section: Perceived Social Support Rumination and Sleep Quality Are Co...mentioning
confidence: 99%
“…It was also found that frail aging adults who spend most of their time indoors in bed do not get exposed to enough illumination throughout the day. A study with 44 participants in Japan measured the subjects’ illumination levels throughout the day for 3 days found that the mean illuminance while indoors was just 201 lux and for bed ridden adults was only 5 ± 11 lux [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, improving and enhancing the mental health of older adults is essential to achieve the goals of healthy aging and active aging in China [ 18 ]. Existing literature has studied the influential factors of the mental health of older adults from the perspectives of individual characteristics [ 19 , 20 , 21 ], social cognition [ 22 , 23 , 24 ], environmental characteristics [ 25 , 26 , 27 ], and so on.…”
Section: Literature Review and Analysis Frameworkmentioning
confidence: 99%